Nonalcoholic Fatty Liver Disease: Clinical Features and Pathogenesis - Basaranoglu, Metin (Gastroenterol Hepatol (N Y), 2006)
Nonalcoholic fatty liver disease (NAFLD) describes a spectrum of liver abnormalities from benign steatosis to nonalcoholic steatohepatitis (NASH). NASH is characterized by chronic and progressive liver pathology and can cause advanced fibrosis, cirrhosis, hepatocellular carcinoma, end-stage liver disease, and liver-related death. Unlike other forms of chronic liver disease, NAFLD is usually associated with insulin resistance and often at least one feature of the metabolic syndrome (obesity, impaired fasting glucose, hypertriglyceridemia, low high-density lipoprotein cholesterol, and hypertension). Although its progression rate may be slower than that of other types of liver disease, the incidence of both NAFLD and its sequelae is increasing throughout the world in parallel with the obesity epidemic. One of the important and unresolved problems is the pathogenesis of hepatocyte injury in NASH. The natural history of NAFLD remains unclear because of the paucity of histologic follow-up studies. Although there have been recent attempts to identify treatments for NAFLD, currently there is no well-established and approved therapy. Lifestyle modifications that include increased exercise and weight reduction address the underlying insulin resistance and may be the best advice for patients.